2008
DOI: 10.1038/ejhg.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inbreeding on fertility in a pre-industrial population

Abstract: Little is known about the effects of inbreeding on reproduction in modern human societies. It appears indeed that biological effects are hidden by socioeconomic factors, which are the major determinants of fertility. It has been established, in particular, that socially induced reproductive compensation tends to homogenize the number of offspring per family in a given population. Besides, in the field of evolutionary biology, a number of empirical and theoretical studies have shown that the effects of inbreedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 43 publications
(38 reference statements)
1
17
2
Order By: Relevance
“…Beyond methodological considerations, we confirmed in this study known associations between increased inbreeding and reduced lung function (PEF), cognitive ability (FIS and MTCIM), and fertility (NCF), which were previously reported, however, using different proxy traits (10,(29)(30)(31). We also replicated the association between inbreeding and decreased height (b UNI − LDMS: −1.71 phenotypic SD for complete inbreeding; P = 0.003) even though it was below the Bonferroni threshold.…”
Section: Discussionsupporting
confidence: 72%
“…Beyond methodological considerations, we confirmed in this study known associations between increased inbreeding and reduced lung function (PEF), cognitive ability (FIS and MTCIM), and fertility (NCF), which were previously reported, however, using different proxy traits (10,(29)(30)(31). We also replicated the association between inbreeding and decreased height (b UNI − LDMS: −1.71 phenotypic SD for complete inbreeding; P = 0.003) even though it was below the Bonferroni threshold.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies have shown that IGF-1R overexpression or constitutive activation is sufficient to induce mammary tumor development in vivo [46]. Our analysis of IGF-1R expression in benign versus malignant breast tissue indicates a significantly higher level of IGF-1R positivity as defined by an Allred score of C7.…”
Section: Discussionmentioning
confidence: 98%
“…As accurate as genome-wide assessments of inbreeding have proven, equally high-quality phenotype data are necessary to detect inbreeding depression. In humans and wild populations, inbreeding depression can be assessed by tracking vital rates--birth rate, mortality rate--in a population over time (Bittles et al, 2002;Robert et al, 2005;Robert et al, 2009;Johnson et al, 2011). In domestic species, additional measures of inbreeding depression include litter size, reproductive success, body size, and performance traits are used (as discussed earlier).…”
Section: Introductionmentioning
confidence: 99%